THE AUDIT AUTHORITY THE STATE AUDIT BOARD OF THE VILLAGE FINANCIAL MANAGEMENT IN SOLOK REGENCY - Budiyono Budiyono; Yusdiyanto Yusdiyanto; Irdham Riyanda (Cepalo, 2023)
Village development is one of the government's agendas in the third nawacita listed in the 2020-2014 RPJMN. Nonetheless, the uncertainty of administrative law related to institutional authority and the mechanism for examining village financial management is still a problem. BPK-RI, as the state financial examiner, has not been explicitly mandated in the package of the State Finance Law to conduct audits of the village government and village finances. This research method was carried out through normative juridical and empirical juridical analysis methods to map the inspection model needed by the village government. The analysis was carried out using the theory of state finances and the theory of state financial audits, and the theory of authority. Research suggests that in the future, an adjustment is needed between the package of Laws on State Finance to align with the package of Laws related to Villages. The results of the study concluded that the authority currently owned by BPK-RI in managing village finances has the potential for arbitrary action (willekeur) by BPK-RI and the potential to submit a lawsuit for authority against BPK-RI in the future. Meanwhile, the village government, represented by the Nagari government in Solok Regency, revealed that the audit carried out by the BPK-RI had been beneficial in encouraging improvements in the performance of the Naga government, nonrequired that the BPK-RI could focus on the SPI audit model and the performance of the Nagari government. Therefore, the ideal inspection model can be carried out through integrated auditing.